Specialized training of children and youngsters in selected sports games - Buchtel, Jaroslav; Kočíb, Tomáš; Tůma, Martin (Acta Universitatis Carolinae. Kinanthropologica, 2013)
The study has two principal goals. The first one is the analysis of personal characteristics of coaches, who function with teams of youth in clubs participating in the top and second to top competitions of adults in handball, tennis and volleyball. Analysis brakes data down following criteria of age, level of education reached and gender. The second goal of our study is the analysis of the sport preparation of children and youth in mentioned sports games on their observation of federations' recommendations about the content of training in respective age groups, including detection of their opinions on the beginning of specialized training for respective playing functions. Research sample was created all-together by 234 coaches (102 volleyball, 69 tennis, 63 handball), who responded to sent non-standard questionnaire with closed and half-opened queries (total rate of return was 67%). Used questionnaire contained eight identifying and five factual questions. Quantitative characteristics are expressed in absolute and relative frequencies, for synoptic presentation of results we have used graphical illustration of responses. Questions concerned players participating in competitions of age groups from about 8 to 19 years. As far as personal composition concerns, the prevailing part of observed sample is created by coaches of age category 30-40 years, out of which about ¼ are women. We have found significant differences among respective games in the educational sphere. While in tennis and volleyball the university educated coaches creates simple majority (65% and 76% respectively), their portion in handball is only about 40%. The representation of P.E. teachers among respective sports games is similarly different – 83% and 76% respectively in tennis and volleyball, on the contrary to 29% in handball. Tennis possesses very low portion of coaches working with category of youngsters (6%). We have found also differences in opinions regarding to the necessity of preparatory phases, i.e. categories preceding younger pupils. Primarily coaches of tennis assume this phase as inevitable. On the contrary we find the distinctive agreement in opinions concerning early specialization – only a narrow minority of coaches is assured about its benefits (8%). Coaches of tennis and volleyball are in agreement as concerns the start of specialization according to playing functions in older pupils category. The selection of one age category in our group of tennis coaches is impossible.
Keywords: Physical Education and Training; volejbal; Male; Tennis; Middle Aged; Adolescent; tenis; Česká republika; Child; vzdělání trenérů; dítě; Adult; dospělí; mužské pohlaví; průzkumy a dotazníky; mladiství; Volleyball; Czech Republic; tělesná výchova; lidé; ženské pohlaví; Sports; Humans; Surveys and Questionnaires; Female; lidé středního věku; sporty; raná specializace